PENGEMBANGAN BAHAN AJAR TEMATIK DI SD/MI BERBASIS PJBL UNTUK MAHASISWA PRODI PGMI - Agustin, Nurul; Pratiwi, Desi Eka (Jurnal Muassis Pendidikan Dasar, 2024)
This research aims to determine the feasibility, learning outcomes and student responses to PJBL-based SD/MI Thematic textbooks for PGMI students at the Al Azhar Menganti Gresik Institute. The development of SD/MI thematic textbooks uses the ADDIE model through several stages, namely, (Analysis, Design, Development, Implementation, Evaluation). From the validation results from material and media experts in the development of SD/MI Thematic textbooks, a percentage of 91.72% was obtained from material experts and media experts with a total of 92%. The use of thematic textbooks in SD/MI is able to develop students' critical thinking and independence in expressing opinions as evidenced by the results of posts with a score of 95.45% which is supported by student responses with a score of 84%. From all the data obtained, it shows that the development of Thematic Textbooks in SD/MI is feasible to be applied to the learning of Thematic courses in SD/MI.